The Canons of Antioch - Stephens, C. W. B. (Studies in church history, 2007)
The death of Constantine in AD 337 brought forth a struggle between leading bishops of the eastern and western empire which proved crucially important in the development of ecclesiastical politics. Athanasius of Alexandria was one of several controversial bishops who, having been deposed during Constantine’s reign, were re-instated by the new emperors after the change of regime which followed his death. As with other cases, Athanasius’s restoration was fiercely contested within the Church, where many bishops felt that an imperial edict of repeal could not overrule a just and final deposition by an ecclesiastical synod. He therefore found himself quickly ejected from Alexandria by rival ecclesiastical powers. The numerous theological and polemical writings which Athanasius produced following this period became enormously influential. Historians still widely follow his version of events, seeing the struggle among bishops which his restoration sparked as centred on an ‘Arian versus orthodox’ theological battle, whereby western supporters of Athanasius fended off eastern attacks against the divinity of Christ. This approach is dangerous. Although the Alexandrian’s writings are both detailed and prolific, they can hardly be called disinterested. Throughout his histories, bishops whom he attacks most fervently as Arians are precisely those who contested his own legitimacy as a bishop.